CUBISM "TWO FACE OF THE GIRLS" - Melda Eksiyana; Ruth Ambarsari; Amin Sulistiyowati (Canthing, 2022)
The fashion design in this Final Project aims to create a special party fashion design that combines the source of ideas and selected fashion styles. The source of the idea for this design is Cubism "Two Face of the Girls" itself is poured into clothing with the application of pacth wrok and using traditional lurik material, while the fashion style is Harajuku Style using original clothing from Japan such as Yukata and Kimono. The type of clothing chosen is a special themed party dress. The material used in this design is linen cotton and hemp cotton for the Cubism motif. The colors of the material in this design use secondary colors. Keyword: Cubism ( Two face of the girls ).